2016
DOI: 10.1002/glia.22977
|View full text |Cite
|
Sign up to set email alerts
|

Nuc‐ErbB3 regulates H3K27me3 levels and HMT activity to establish epigenetic repression during peripheral myelination

Abstract: Nuc‐ErbB3 an alternative transcript from the ErbB3 locus binds to a specific DNA motif and associates with Schwann cell chromatin. Here we generated a nuc‐ErbB3 knockin mouse that lacks nuc‐ErbB3 expression in the nucleus without affecting the neuregulin‐ErbB3 receptor signaling. Nuc‐ErbB3 knockin mice exhibit hypermyelination and aberrant myelination at the paranodal region. This phenotype is attributed to de‐repression of myelination associated gene transcription following loss of nuc‐ErbB3 and histone H3K27… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
7
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 57 publications
1
7
1
Order By: Relevance
“…Ness and colleagues (2016) identify Nuc-ErbB3, a nuclear variant of ErbB3, as a DNA-binding protein that promotes H3K27me3 at gene promoters presumably by activating the HMT EZH2. This study reports that loss of Nuc-ErbB3 (constitutive mouse mutant) leads to developmental hypermyelination [49]. Consistently, ablation of the PRC2 subunit Eed in immature SCs (using floxed Eed and P0-Cre mouse lines), that leads to inactivation of the PRC2 complex (mediating H3K27me3 through its HMT EZH2), results in hypermyelination in adults [50 ].…”
Section: Involvement Of Repressive Histone Methylation Marks In Regulsupporting
confidence: 64%
“…Ness and colleagues (2016) identify Nuc-ErbB3, a nuclear variant of ErbB3, as a DNA-binding protein that promotes H3K27me3 at gene promoters presumably by activating the HMT EZH2. This study reports that loss of Nuc-ErbB3 (constitutive mouse mutant) leads to developmental hypermyelination [49]. Consistently, ablation of the PRC2 subunit Eed in immature SCs (using floxed Eed and P0-Cre mouse lines), that leads to inactivation of the PRC2 complex (mediating H3K27me3 through its HMT EZH2), results in hypermyelination in adults [50 ].…”
Section: Involvement Of Repressive Histone Methylation Marks In Regulsupporting
confidence: 64%
“…By analyzing the promoters of the type I and type III transcripts of Nrg1 , we found that H3K27me3 mediates repression of Nrg1 and there is increased expression of the type I Nrg1 transcript in the uninjured Eed cKO nerves, indicating a mechanism by which type I Nrg1 is repressed in uninjured nerve. Interestingly, NRG1 increases the expression of nuc-ErbB3 (a nuclear variant of the NRG1 receptor, ErbB3), which has transcriptional activity by modulating H3K27me3 level in Schwann cells (Adilakshmi et al 2011; Ness et al 2016). However, nuc-ErbB3 likely has other activities since the phenotype and gene expression changes that we observe in the Eed knockout differ in several respects.…”
Section: Discussionmentioning
confidence: 99%
“…Gray shading indicates H3K27me3 occupancy of genes in peripheral nerves of uninjured or post-injury conditions. See Supporting Information Table 6 for expression fold changes by Eed cKO among PRC2-deficient MPNST genes and H3K27me3 peak score [Color figure can be viewed at wileyonlinelibrary.com] expression of nuc-ErbB3 (a nuclear variant of the NRG1 receptor, ErbB3), which has transcriptional activity by modulating H3K27me3 level in Schwann cells (Adilakshmi, Ness-Myers, Madrid-Aliste, Fiser, & Tapinos, 2011;Ness et al, 2016). However, nuc-ErbB3 likely has other activities since the phenotype and gene expression changes that we observe in the Eed knockout differ in several respects.…”
Section: Discussionmentioning
confidence: 99%
“…In Nuc‐ErbB3 knockin mouse, which is a variant of ERBB3 that is expressed in the nucleus of Schwann cells, Ness found that NUC‐ERBB3 could significantly decrease the activation of histone H3K27me3 methyltransferase (HMT), reduce level of H3K27me3, and eventually lead to aberrant myelination (Ness et al., ).…”
Section: Other Histone Modifications In Myelinating Cellsmentioning
confidence: 99%
“…In Nuc-ErbB3 knockin mouse, which is a variant of ERBB3 that is expressed in the nucleus of Schwann cells, Ness found that NUC-ERBB3 could significantly decrease the activation of histone H3K27me3 methyltransferase (HMT), reduce level of H3K27me3, and eventually lead to aberrant myelination (Ness et al, 2016). Petrilli et al (2013) Except for lysine methylation, protein arginine methyltransferase, PRMT1 and PRMT5, have been identified playing critical roles during OL differentiation.…”
Section: Modifications In Myelinating Cellsmentioning
confidence: 99%